People Movement Characteristics Based on an Evacuation Test - Martin Lopusniak; Dusan Katunsky (Communications - Scientific letters of the University of Zilina, 2014)
Modelling of the evacuation of people is the only method leading to a proper design of emergency escape routes from buildings. The background details necessary for modelling can only be obtained from actual incidents or evacuation tests. The paper presents the results of an evacuation test carried out in a university environment with respect to an announced evacuation. The introduction of the paper describes the scope of the test, physiological characteristics of the participants, the geometry and the environment. The analysis of the evacuation test focuses on the movement of people and the flow. The analysis of the results showed that the values recorded in the test are identical to those used in evacuation models; nevertheless, they differ from the calculation model and values used in the national prescriptive code.